Cross-Reactivity in histoplasma capsulatum variety capsulatum antigen assays of urine samples from patients with endemic mycoses (1997)
ABSTRACT: We evaluated cross-reactivity in the antigen assay used for the diagnosis of histoplasmosis by testing urine samples from patients with disseminated fungal infections. The mycoses chosen for this study were selected on the basis of the observation that during clinical testing, cross-reactions may occur between Histoplasma capsulatum var. capsulatum, Paracoccidioides brasiliensis, Blastomyces dermatitidis, Coccidioides immitis, and Penicillium marneffei. We detected antigen in 12 of 19 patients with blastomycosis, 8 of 9 with paracoccidioidomycosis, in 17 of 18 with P. marneffei infection, and in one with disseminated H. capsulatum var. duboisii infection. Cross-reactions were not observed in the assays for six patients with disseminated coccidioidomycosis. Cross-reactivity between the agents of other endemic mycoses should be considered in interpreting a positive H. capsulatum var. capsulatum antigen assay. Antigen detection may provide a rapid, provisional diagnosis for patients with serious infections caused by one of these organisms.